The role of social norms and informal sanctions in catch-and-release angling - Stensland, Stian; Aas, Øystein (Fisheries Management and Ecology, 2014)
This study focuses on norms and informal sanctions of catch-and-release angling and their implications for fishery management. A Web-based questionnaire of Atlantic salmon, Salmo salar L., anglers in the Lakselva River, Norway, yielded 656 answers (response rate 68 %). Anglers were segmented into four subgroups: catch and release, keeper, something else, trophy angler. In all groups, the reward (positive feeling) was high and punishment was low for releasing a large salmon as expressed by the intensity of self-sanctions. All groups saw keeping a large salmon mostly as a rewarding experience, although the C&R and trophy segments reported less rewards and more ‘punishment’ for keeping. There is evidence for both a medium strength C&R norm and a weak keep norm in this fishery, receiving different ascriptions between angler groups. The results help understand angler group conflicts and explain how angling behaviour is formed, thereby helping management agencies achieving angler satisfaction. catch orientation, human dimensions, motivation, nature-based tourism, recreational fishing, sport fishing. acceptedVersion